Comparing the meanings of living with advanced breast cancer between women resilient to distress and women with persistent distress: a qualitative study. Issue 2 (6th April 2016) - Lam, W. W. T.; Yoon, S. W.; Sze, W. K.; Ng, A. W. Y.; Soong, I.; Kwong, A.; Suen, D.; Tsang, J.; Yeo, W.; Wong, K. Y.; Fielding, R.
Abstract: Background: Most women with advanced breast cancer (ABC) show little distress, but about one in ten show persistent distress over time. It remains unclear if meanings ascribed by patients to ABC differentiate these distress trajectories. Study aims: This qualitative study (a) compared illness meanings of ABC between women with persistent psychological distress and those with low/transient distress, and (b) examined how illness meanings might influence coping strategies. Methods: The sample was drawn from a prior quantitative study exploring psychological distress trajectories following ABC diagnosis. Overall, 42 Cantonese‐ or Mandarin‐speaking Chinese women diagnosed with locally advanced or metastatic ABC were recruited based on their distress trajectory status (low‐stable, transient, or persistent distress). Interviews were recorded, transcribed, and analyzed following grounded theory approach using simultaneous analysis. Results: Women with persistent distress viewed their diagnosis as another blow in life, the illness was global, permeating every aspect of their life. Maladaptive rumination and thought suppression were common responses to illness demands. These women had poor social support. A sense of demoralization stood out in their narratives. In contrast, women with transient/low‐stable distress encapsulated the illness, with minimum impacts of their life. They did not evidence dysfunctional repetitive thoughts. Living in a supportive environment, they were able to accept and/or live in the present‐moment. Conclusions: Rumination, thought suppression, social constraints, and pre‐existing exposure to life stress may be potential risks for chronic distress in response to advanced breast cancer. Persistent and transient distress responses to cancer may have different underpinnings. Copyright © 2016 John Wiley & Sons, Ltd.